PERBANDINGAN BIAYA RIIL DENGAN TARIF INA-CBG’S PENYAKIT STROKE PADA ERA JAMINAN KESEHATAN NASIONAL DI RS ISLAM SULTAN AGUNG - Ken Wirastuti; Indriyati Hadi Sulistyaningrum; Erwin Budi Cahyono; Arifin Santoso; Zaki Miftahudin (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
The implementation of INA CBG's system is not yet optimal because INA CBG’s rate in fact not yet fulfill hospital real cost. The purpose of this research was to compare the INA-CBG’s rate and real cost and also to look the factors affecting has difference the big real cost in patient with stroke in JKN era at Sultan Agung Islam Hospital between January 2017 and October 2017.Research using descriptive analysis, the data were analysed by Mann-Whitney test was used to compare real cost and INA-CBG’s rate. And the Mann-Whitney followed Kruskal-Wallis to determine the components of the factors affect real costs.There was a difference between the real cost and the INA-CBG's rate for hospitalization of (Rp -12,184,500) and outpatient care of (Rp -1,949,300). Factors that affect the real cost are type of nursing class (0,009), LOS (0,019) and age (0,045).The conclusion of this study is that there was a difference between the real cost and INA-CBG’s rate in patient with stroke in JKN era at Sultan Agung Islam Hospital between January 2017 and October 2017. Factors that affect the big real cost are type of nursing class, LOS and age.